2022
DOI: 10.1029/2021ms002699
|View full text |Cite
|
Sign up to set email alerts
|

The Global Atmosphere‐aerosol Model ICON‐A‐HAM2.3–Initial Model Evaluation and Effects of Radiation Balance Tuning on Aerosol Optical Thickness

Abstract: The Hamburg Aerosol Module version 2.3 (HAM2.3) from the ECHAM6.3‐HAM2.3 global atmosphere‐aerosol model is coupled to the recently developed icosahedral nonhydrostatic ICON‐A (icon‐aes‐1.3.00) global atmosphere model to yield the new ICON‐A‐HAM2.3 atmosphere‐aerosol model. The ICON‐A and ECHAM6.3 host models use different dynamical cores, parameterizations of vertical mixing due to sub‐grid scale turbulence, and parameter settings for radiation balance tuning. Here, we study the role of the different host mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…The minimum CDNC threshold (10 cm −3 ) prevents the occurrence of clouds with nonzero cloud fraction but very few cloud droplets. This threshold is also used in ECHAM6.3 (Salzmann et al., 2022) and showed impacts on aerosol ERF and EffCS (Neubauer et al., 2019). The more negative autoconversion CDNC exponent enhances the sensitivity of autoconversion rate to a CDNC change, and the increased accretion enhancement factor increases the accretion rate of cloud droplets by rain.…”
Section: Physical Processes Contributing To Evolution Of Cloud Feedba...mentioning
confidence: 99%
“…The minimum CDNC threshold (10 cm −3 ) prevents the occurrence of clouds with nonzero cloud fraction but very few cloud droplets. This threshold is also used in ECHAM6.3 (Salzmann et al., 2022) and showed impacts on aerosol ERF and EffCS (Neubauer et al., 2019). The more negative autoconversion CDNC exponent enhances the sensitivity of autoconversion rate to a CDNC change, and the increased accretion enhancement factor increases the accretion rate of cloud droplets by rain.…”
Section: Physical Processes Contributing To Evolution Of Cloud Feedba...mentioning
confidence: 99%
“…Salzmann et al. (2022) recently reported on the impact of moist convection parameter settings on wet deposition and as a result on AOD.…”
Section: Simulation Campaignmentioning
confidence: 99%
“…This might be an unintended consequence of intensive cloud and precipitation parameter tuning for EAMv2. Salzmann et al (2022) recently reported on the impact of moist convection parameter settings on wet deposition and as a result on AOD.…”
Section: Aerosolsmentioning
confidence: 99%
“…The modal aerosol module "HAM" that employs seven log-normal aerosol modes is used interactively in the ECHAM model since almost two decades (Zhang et al 2012 ;Tegen et al 2019). Recently it is also implemented in the successor of ECHAM, the ICON model (Salzmann et al 2022). The two models with profoundly different dynamical cores share the same physics package.…”
Section: Perspectivesmentioning
confidence: 99%